Self contained Food Sample Homogenization Filter Bag for Microbial Analysis - C., Jayaprahash; JH., Lakshmana; J., Joseph Kingston (Defence Life Science Journal, 2020)
The complexity of food materials owing to the diverse matrices and biochemical composition poses challenge to microbiologists especially to identify the microbial contamination at low level. The present study describes the development and evaluation of a ready to use self-contained food sample homogenization bag (All-In-Bag) with the required sterile diluent and an in-built filter for subsequent clarification of the homogenate for microbiological analysis. Three-ply non-foil laminate comprising outer alumina oxide coated polyester film, middle nylon and inner polypropylene layers were used for the outer layers while non-woven polypropylene sheet with of 50 μ to 100 μ size porosity was sandwiched between the laminated sheets to restrain the food debris but allow the microbial cells to pass through across along with the diluent. The homogenization bag along with the diluent was sterilized by thermal (retort) processing with F0 value (lethality value) of 12 to ensure the sterility of diluent during storage. The effectiveness of the All-in-Bag for the homogenisation of different food sample matrices for microbiological analysis was compared with BagPage®+ bag. All-in-Bag withstood the shearing action during sample paddling in the bag mixer/stomacher and no significant difference was observed for both aerobic plate count. Spike and recovery of E. coli from the different food matrices indicating absence of interference for microbial recovery in newly developed All-in-Bag. The All-in-Bag, the first of its kind with 12 months shelf life does away with the requirement of sterile diluent preparation and additional steps for the clarification of the homogenate and thus making microbial food quality analysis easier in places with limited resources.